High-resolution imaging for in-situ non-destructive testing by quantitative lensless digital holography - Ruiz-Cadalso, Daniel; Furlong, Cosme (Frontiers in Photonics, 2024)
Quantitative imaging technologies for in-situ non-destructive testing (NDT) demand high-resolution, wide-field, and stable metrology capabilities. Moreover, live processing and automation are vital for real-time quality control and inspection. Conventional methods employ complex optical setups, resulting in large, immobile systems which can solely operate within controlled environmental conditions due to temporal instabilities, rendering them unsuitable for in-situ measurements of microto nano-scale physical phenomena. This article delves into the multiphysics application of lensless digital holography, emphasizing its metrological capacity for various in-situ scenarios, while acknowledging and characterizing the differing constraints imposed by various physical phenomena, both transient and steady-state. The digital reconstruction of holograms is computed in real-time, and numerical focusing capabilities allow for instantaneous retrieval of the optical phase at various working distances without the need of complex optical setups, making lensless digital holography well-suited for in-situ quantitative imaging under various types of environments. Current NDT capabilities are demonstrated, including high-resolution and real-time reconstructions, simultaneous measurements for comparative metrology, and practical applications ranging from vibrations and acoustics to thermo-mechanics. Furthermore, methodologies to enhance overall metrology capabilities are exploited, addressing the study of existing physical phenomena, thereby expanding the applicability of holographic techniques across diverse industrial sectors.